The role of emotional and factual retelling on memory accuracy in eyewitness testimony - Lau, Choon Ning (Universiti Malaysia Sarawak (UNIMAS), 2015)
Eyewitnesses are normally talking about the crimes they have seen and involved in based on their memory. Different ways on how an eyewitness talks about the crime can influence the information collected. This research is aimed to investigate the differences of pre-retelling and post-retelling on memory accuracy and error between emotion, factual and control conditions. 30 participants were involved in the research. Those participants were requested to watch a video about a robbery for 3 minutes and recall the events by listing down the related details. Then, they were assigned to three different retelling conditions which are factual, emotional and control condition. The participants would be retelling the events in different ways based on the conditions. Stratified random sampling technique was used in this research so that the numbers of male and female participants were equal. Repeated measure ANOYA was used to test the hypotheses ofthe study. Result showed that emotion can affects the eyewitness memory significantly.